Embarazos en adolecentes, conocimientos, actitudes y prácticas vinculados a la sexualidad en la parroquia Moraspungo en el año 2019. - Barrionuevo Paredes, Pablo Javier (2020)
The purpose of this research is to carry out a project based on the implementation of a training plan on prevention of adolescent pregnancy, which is expected to serve as a development alternative for the Moraspungo parish corresponding to the Pangua canton, a project that is related to with the experience of responsible sexuality and without prejudice in adolescents, which will allow them to lead a responsible and healthy life. The training plan for adolescent men and women on prevention of adolescent pregnancy in the parish will always be of vital importance in the development of knowledge, attitudes and practices related to sexuality, at the same time it allowed us to focus on strengths through good living, pregnancy prevention as a protective factor, health education, promotion of a life project to influence assertive decisions throughout life regarding human sexuality